Tantangan Menjadi Guru Matematika dengan Kurikulum Merdeka Belajar di Masa Pandemi Omicron Covid-19 - Hanter Manik; Agustina C B Sihite; Farida Sianturi; Simon Panjaitan; Agusmanto J B Hutauruk (Edumaspul: Jurnal Pendidikan, 2022)
“Teachers are the main key to success in producing a quality and quality Indonesian gold generation in 2045. Therefore, teachers must have the ability to design learning to be meaningful and useful” (Pujiasih, 2020). As a Mathematics Teacher, you must always guide students regarding how to really learn (learning how to learn) and how to solve every problem in front of them (learning how to solve problems) that will be utilized and used in the future. Independent learning curriculum is a new step that makes some changes in terms of learning. During the COVID-19 pandemic, which has so far returned with the Omicron variant, all teachers/educators are required to turn their brains around to provide optimal online/virtual learning, as well as students who have to adapt to online/virtual learning and have to be extra in understanding the material. . The success of teachers and students in optimally practicing online learning in an independent learning curriculum will also have an impact on the development of students' thinking power. In online learning practices, with an independent learning curriculum, Mathematics educators/teachers have an important role, namely not only providing material but character education is also very important and useful for student behavior, by means of teachers not only providing material for free but can provide examples to students, so that students are able to be dedicated and innovate in the independent learning curriculum.